Memahami Ideologi Pendidikan Dalam Perspektif Al – Qur’an - Desita Nur Azizah (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2017)
Theoretically ideology is the theoretical foundation and philosophical view that provides operational direction. In its development there are current of three major ideology that influence education, namely: conservative, liberal, and critical. Traditional education systems tend to use conservative ideology as the basis for their education. Meanwhile, modern education that is currently growing rapidly in the pace of globalization is guided by liberacy the education management by carrying the spirit of high humanism. On the other hand, Islam as a religious building that carries the concept of rahmatan lil 'alamin basically has the concept of humanist value that is actually available in the Qur'an. It's just how humans can dig up and maximize their use in educational studies appropriately and to achieve the ideal educational concept needs to be developed more broadly. Thus, the concept or ideology of Islamic education actually already exists in the Qur'an and how human can maximize their potential to explore these sciences.